1984
DOI: 10.1093/nar/12.20.7787
|View full text |Cite
|
Sign up to set email alerts
|

Reversion to neurovirulence of the live-attenuated Sabin type 3 oral pollovirus vaccine

Abstract: The complete nucleotide sequence has been determined of a strain of poliovirus type 3, P3/119, isolated from the central nervous system of a victim of fatal vaccine-associated poliomyelitis. Comparison of this sequence with those obtained previously for the Sabin type 3 vaccine, P3/Leon 12a1b and its neurovirulent progenitor, P3/Leon/37, reveals that these three strains are on a direct geneaological lineage and therefore that P3/119 is a bona fide revertant of the vaccine. P3/119 differs in sequence from its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(87 citation statements)
references
References 16 publications
4
83
0
Order By: Relevance
“…Fluorescently-labeled ssDNA for hybridization was prepared form each poliovirus serotype as described above and elsewhere (Laassri et al, 2005). Results of our study (Laassri et al, 2006) show that many stool samples from healthy children one week after OPV vaccination contained different percentages of revertants, consistent with earlier observations based on conventional methodology (Cann et al, 1984;Kew et al, 2002;WHO, 2002). The oligonucleotide microarrays simultaneously detected and discriminated between vaccine and revertant sequences and allowed the quantitation of reversions in the 5'-UTRs of all 3 serotypes of poliovirus.…”
Section: Microarray Assay For Quantitation Of Known Virulent Mutationssupporting
confidence: 85%
See 1 more Smart Citation
“…Fluorescently-labeled ssDNA for hybridization was prepared form each poliovirus serotype as described above and elsewhere (Laassri et al, 2005). Results of our study (Laassri et al, 2006) show that many stool samples from healthy children one week after OPV vaccination contained different percentages of revertants, consistent with earlier observations based on conventional methodology (Cann et al, 1984;Kew et al, 2002;WHO, 2002). The oligonucleotide microarrays simultaneously detected and discriminated between vaccine and revertant sequences and allowed the quantitation of reversions in the 5'-UTRs of all 3 serotypes of poliovirus.…”
Section: Microarray Assay For Quantitation Of Known Virulent Mutationssupporting
confidence: 85%
“…Among the best characterized attenuating mutations in the OPV Sabin strains are mutations located in the Internal Ribosome Entry Site (IRES) of the 5'-untranslated region (5'-UTR) (Minor, 1992) (Figure 3). These mutations have been identified in Sabin type 3 poliovirus (472U→C) (Cann et al, 1984), as well as type 2 (481A→G) (Macadam et al, 1993), and type 1 (480G→A and 525U→C) (Otelea et al, 1993); they are believed to selectively affect initiation of translation of viral polyprotein in neuronal cells (Guest et al, 2004;Svitkin et al, 1990). Previously was shown that the content of these revertants www.intechopen.com Viral Genomes -Molecular Structure, Diversity, Gene Expression Mechanisms and Host-Virus Interactions 188 was low in vaccine batches that failed the monkey neurovirulence test (Chumakov et al, 1991).…”
Section: Microarray Assay For Quantitation Of Known Virulent Mutationsmentioning
confidence: 99%
“…Comparative sequence analysis of three poliovirus type 3 strains differing in neurovirulence revealed that a single nucleotide in the 5' UTR (position 472) correlated with the virulent phenotype (Stanway et al, , 1984bCann et al, 1984). This work was extended by partial sequence analysis of other strains and subsequently by in vitro manipulation of the viruses which indicated that the C to U change observed between the virulent and attenuated strains was a major determinant of attenuation (Evans et al, 1985;Westrop et al, 1989).…”
Section: G Stanwaymentioning
confidence: 90%
“…Plasmid DNA isolated from strongly hybridizing colonies was further characterized by restriction endonculease mapping and cross-hybridization. EV70 eDNA was subcloned into M13mp8 or M13mp9 by a combination of randomly sheared and restriction endonuclease DNA fragments as described previously (Stanway et al, 1984). The sequence of eDNA inserts was determined by the dideoxynucleotide method and the data were assembled and analysed using published computer programs (Staden, 1980).…”
Section: Methodsmentioning
confidence: 99%
“…Sequences used for comparative purposes were for poliovirus type 1 (P1) Mahoney (Kitamura et al, 1981), P1 Sabin (Nomoto et al, 1982), P2 Lansing (La Monica et al, 1986), P2 Sabin (Toyada et al, 1984), P3/Leon , P3/119 (Cann et al, 1984), P3/Finland (Hughes et al, 1986), P3/Sabin (Stanway et at., 1984a), coxsackievirus A9 (CA9) Griggs (Chang et al, 1989), coxsackievirus CA21 Coe (Hughes et al, 1989), coxsackievirus B 1 (CB 1) (Iizuka et al, 1987), CB3 Nancy (Lindberg et al, 1987), CB4 JVB (Jenkins et al, 1987), swine vesicular disease virus (SVDV) H/3 '76 (Inoue et al, 1989), SVDV UKG/27/72 (Seechurn et aL, 1990), bovine enterovirus (BEV) VG-5-27 (Earle el al., 1988), BEV PSU87 and BEV RM2 (L. Hoey, unpublished results), human rhinovirus (HRV) 1A (G. Cordova; see Kim et al, 1989), HRV1B (Hughes etal., 1988), HRV2 (Skern etal., 1985), HRV9 (Leckie, 1988), HRV14 (Stanway et al, 1984b), HRV85 (G. Stanway, unpublished results) and HRV89 (Duechler et al, 1987).…”
Section: Methodsmentioning
confidence: 99%